Pengaruh Rekrutmen dan Pelatihan terhadap Kinerja Pegawai dengan Strategi SDM Sebagai Variabel Moderasi - Rahadi, Dedi Rianto; Selasih, Sekar; Putri, Syifa Anisa Indah (Universitas Sultan Ageng Tirtayasa, 2024)
The purpose of the study is to analyze and explain the results of the effect of recruitment and training on employee performance with HR strategy as a moderating variable. This research applies a quantitative approach by using a tool called Smart-PLS and the SEM-PLS analysis method. The data used as a reference is also primary data collected through surveys. The sample used is a saturated sample where the entire population is taken as a sample. The results of this study are recruitment has no significant effect on employee performance, training has no significant effect on employee performance, HR strategy moderates the impact of recruitment on employee performance, HR strategy moderates the impact of training on employee performance, and HR strategy has a significant effect on employee performance.